Antioxidant and Nutritional Potential of Artichoke (Cynara scolymus L.) By-Product Extracts in Fat-Replaced Beef Burgers with Hydrogel Emulsions from Olive Oil - Pablo Ayuso; Jhazmin Quizhpe; María de los Ángeles Rosell; Rocío Peñalver; Gema Nieto (Applied Sciences)
Beef burger consumption has been questioned due to the burgers’ high levels of saturated fatty acids and the use of synthetic additives for preservation. In order to improve the acceptability and health benefits of this product, two functional ingredients, artichoke and extra-virgin olive oil (EVOO), have been used to formulate four different beef burgers: a control burger (CB), a fat-replaced burger with an EVOO emulsion (FRB), and two FRB formulations with the incorporation of enzymatically treated (FRB-TAE) or untreated (FRB-AE) artichoke extract. Fat replacement significantly affected the lipid profile of the burgers, increasing oleic acid levels and n-3 PUFA such as α-linolenic and eicosapentaenoic acids. Artichoke incorporation exerted beneficial effects on the antioxidant activity, as well as on the total phenolic content of the reformulated burgers, leading to a decrease in color changes, lipid and protein oxidation after 3 days of storage at 4 °C, as well as reducing the formation of volatile compounds such as hexanal, 2,3-Octanedione, or 1-Octen-3-ol. No differences were found between formulations for the sensory parameters studied. These results demonstrate a possible revalorization of artichoke by-products by improving the nutritional properties of beef burgers, revealing a potential application as a higher value-added ingredient in the meat industry.